Assessment Report on Chinese Primary School Students$1 (BAcademic Achievements 4 Subjects of Grade 6 in Primary School Taken as Examples - Tian, Huisheng; Sun, Zhichang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2019)
This book is a report on the academic achievement assessment of Grade-6 students in primary school with a large-scale sample for the first time since the new curriculum reform. This report consists of the general report, reports on the four subjects of Chinese, Mathematics, Science and Morality and Society, the questionnaire survey report and assessment instruments. This report states the complexion of students$1 (Bacademic achievement including achievements and shortcomings and proposes some targeted suggestions. The methods and assessment instruments have important reference value for future academic achievement assessment.s
The General Report on Evaluation of Students' Achievements -- The Subject Reports on Evaluation of Students' Achievements -- The Survey Report on the effective factors of Students' Achievements -- Subject Assessment Instruments.
Keywords: Assessment; Church and education; Assessment, Testing and Evaluation; Religion and Education